Assessment of Environmental Risk from the Project Team's Perspective in Electrical Transmission Line Installation Projects. (June 2017) - Parihar, Shwetank; Bhar, Chandan; Srivastava, Nishit Kumar
This article represents a methodology in which the overall environmental risks can be assessed without much need of secondary data. The method exemplifies on collection of risk data on the basis of pre-decided risk factors in which the project team members are asked to give opinion about various risk factors. Since the main risk management team has already given various pre-defined risk sectors the collective opinion derived gives true value of risk, and the involvement of local workers give an edge over others since they have vast knowledge of geographical factors and this is how their knowledge can be scientifically used to determine environmental risk which is a very true estimation of real risk value. This article has successfully identified factors and scaled them up with the help of a questionnaire-based study. Moreover, different levels of management also pose different environment risk priorities which is also analysed in this article.